Cell formation effects on the burning speeds and flame front area of synthetic gas at high pressures and temperatures. (1st March 2017) - Askari, Omid; Elia, Mimmo; Ferrari, Matthew; Metghalchi, Hameed
Graphical abstract: Highlights: Effect of cell formation on burning speed and flame surface area is investigated. A new developed non-dimensional number called cellularity factor is introduced. Cellular burning speed and mass burning rate are calculated using differential based multi-shell model. Flame instability is studied using thermo-diffusive and hydrodynamics effects. Power law correlations are developed for cellular burning speeds and mass burning rates. Abstract: Cellular burning speeds and mass burning rates of premixed syngas/oxidizer/diluent (H2 /CO/O2 /He) have been determined at high pressures and temperatures over a wide range of equivalence ratios which are at engine-relevant conditions. Working on high pressure combustion helps to reduce the pollution and increase the energy efficiency in combustion devices. The experimental facilities consisted of two spherical and cylindrical chambers. The spherical chamber, which can withstand high pressures up to 400 atm, was used to collect pressure rise data due to combustion, to calculate cellular burning speed and mass burning rate. For flame structure and instability analysis the cylindrical chamber was used to take pictures of propagating flame using a high speed CMOS camera and a schlieren photography system. A new differential based multi-shell model based on pressure rise data was used to determine the cellular burning speed and mass burning rate. In this paper, cellular burning speed and mass burning rate of H2 /CO/O2 /He mixture have been measured for a wide range of equivalence ratios from 0.6 to 2, temperatures from 400 to 750 K and pressures from 2 to 50 atm for three hydrogen concentrations of 5, 10 and 25% in the syngas. The power law correlations for cellular burning speed and mass burning rate were developed as a function of equivalence ratio, temperature and pressure. In this study a new developed parameter, called cellularity factor, which indicates the cell formation effect on flame surface area and burning speed has been introduced. The total flame surface area and cellularity factor for syngas at high pressures and temperatures have been calculated by combining the multi-shell model via the experimental pressure data with free flat flame simulation using detailed chemical mechanism. The results show that the cellularity factor has a positive relation to pressure, equivalence ratio and hydrogen concentration while it has a negative dependency to temperature.